Redox and Epigenetics in Human Pluripotent Stem Cells Differentiation - Giallongo, Sebastiano; Rehakova, Daniela; Raffaele, Marco; Lo Re, Oriana; Koutna, Irena; Vinciguerra, Manlio (Antioxidants & redox signaling, 2021)
Significance: Since their discovery, induced pluripotent stem cells (iPSCs) had generated considerable interest in the scientific community for their great potential in regenerative medicine, disease modeling, and cell-based therapeutic approach, due to their unique characteristics of self-renewal and pluripotency. Recent Advances: Technological advances in iPSC genome-wide epigenetic profiling led to the elucidation of the epigenetic control of cellular identity during nuclear reprogramming. Moreover, iPSC physiology and metabolism are tightly regulated by oxidation-reduction events that mainly occur during the respiratory chain. In theory, iPSC-derived differentiated cells would be ideal for stem cell transplantation as autologous cells from donors, as the risks of rejection are minimal. Critical Issues: However, iPSCs experience high oxidative stress that, in turn, confers a high risk of increased genomic instability, which is most often linked to DNA repair deficiencies. Genomic instability has to be assessed before iPSCs can be used in therapeutic designs. Future Directions: This review will particularly focus on the links between redox balance and epigenetic modifications-in particular based on the histone variant macroH2A1-that determine DNA damage response in iPSCs and derived differentiated cells, and that might be exploited to decrease the teratogenic potential on iPSC transplantation. Antioxid. Redox Signal. 34, 335-349.
Keywords: nádorová transformace buněk; oxidační stres; DNA Methylation; Mitochondria; přeprogramování buněk; metylace DNA; nestabilita genomu; Oxidative Phosphorylation; Pluripotent Stem Cells; epigeneze genetická; buněčná diferenciace; Cell Transformation, Neoplastic; buněčná sebeobnova; Genomic Instability; Induced Pluripotent Stem Cells; transplantace kmenových buněk; pluripotentní kmenové buňky; Epigenesis, Genetic; oxidace-redukce; indukované pluripotentní kmenové buňky; lidé; Stem Cell Transplantation; Humans; Regenerative Medicine; regenerativní lékařství; Oxidation-Reduction; Oxidative Stress; Cellular Reprogramming; oxidativní fosforylace; mitochondrie; Cell Differentiation; Cell Self Renewal